A study of mathematical communication ability in writing on real numbers and polynomials of grade 10 students - Warisa Sakuntanat; Montri Thongmoon (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Mathematical communication is the clear expression of ideas using math language and symbols, either in speech or writing. Without effective writing skill, students may not write steps of problem-solving clearly, and this leads to confusion and ineffective learning. This negatively affects performance in academic work since mathematics is based on logical progression and effective communication can lead to misunderstood problems and incorrect solutions.Aims: This research aims to study the mathematical communication ability in writing, focusing on their ability to use mathematical language and symbols to express concepts.Methods: Quantitative survey was conducted by defining research questions, selecting 40 Grade 10 students from Sarakhampittayakhom School, designing a mathematical communication ability test in writing, distributing the test, collecting post-instruction data, analyzing the data using descriptive statistics, and presenting the research results.Result: Students score an average of 6 out of 16 points (37.50%), with a standard deviation of 2.80. The test focuses on their ability to use mathematical language, symbols, and explanations in problem-solving. While 17.5% have good writing and reasoning ability, 82.5% found it difficult due to limited understanding, low confidence, and insufficient practice, resulting in unclear communication and disorganized thought processesConclusion: Students' mathematical writing ability remains below 50%, with notable score disparities. Developing this skill is essential for effective learning. Teachers enhance mathematical writing through problem-solving explanations, structured writing practices, and precise terminology. Identifying the causes of these disparities supports more effective instruction, while ongoing research explores contributing factors and teaching strategies for skill development.